Pengelolaan Konten Instagram dalam Kampanye Digital untuk Meningkatkan Minat Generasi Z terhadap Layanan Transpakuan Bogor - Muhammad Avicenna; Vivien Febri Astuti; Fahmi Fuad Cholagi (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study discusses the production of digital campaign content for Perumda Transpakuan Bogor through Instagram and videotron as part of public transportation communication strategies targeting Generation Z. The study aims to analyze and implement digital content production processes that are visually engaging, informative, and relevant to young audiences. This research used a qualitative descriptive approach with a project-based applied research orientation. Data were collected through participatory observation, documentation, and Instagram Insight analysis. The project resulted in nine Instagram contents in the form of reels, carousel posts, infographics, and interactive posts, as well as one public service advertisement video for videotron media. The findings show that the use of storytelling, relatable visuals, and short-form video formats effectively increased audience reach and engagement. Instagram reels became the most effective format in attracting Generation Z audiences, while videotron strengthened message distribution in public spaces. The study implies that integrating social media and digital outdoor media can support more effective public communication campaigns for public transportation services.